De véritables jumelles parmi les statues privées de temples aux époques tardives - Perdu, Olivier (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2020)
The similarity between statues is a phenomenon that concerns royal qr divine statuary, but also private statuary, even· if examples are less numerous. Among the private statues, there are examples of identical appearance as early as the Middle Kingdom, the differences are lying in the content of the inscriptions. During the Late Period, similar cases can be found. There are also statues which show similarity in their inscriptions. In addition, contrary to a common belief, real twin statues do exist, both in their appearance and their inscriptions. The cases reported concern prominent figures of the 26th Dynasty, such as the chiefs of the southern borders Wahibre and Neshor.